IMPLEMENTASI KEBIJAKAN PENGARUSUTAMAAN GENDER DALAM PERENCANAAN, PENGANGGARAN RESPONSIF GENDER DI LINGKUP ORGANISASI PERANGKAT DAERAH PROVINSI SULAWESI TENGAH - Bisno, Ilham (Katalogis, 2018)
The research is focused on the implementation of gender mainstreaming policy on gender responsive planning and budgeting framework, specifically on the utilization of gender analysis pathway and gender budget statement, in Central Sulawesi’s Provincial Government Organization. It is a descriptive qualitative research gender analysis pathway and gender budget statement, utilizing Van Meter and Van Horn’s theory on policy implementation, which include standard factors and policy aim, resource, interorganizational communication and activity enhancement, agent characteristics, socioeconomic situations and implementator disposisition. The reasearch shows that gender mainstreaming policy has not been fully implemented, as seen from the large number of government organization in Central Sulawesi’s government that haven’t utilized both. This results in overall lack of gender sensitivity in planned activities and budget alocated, which in turn leads to lower gender development index and gender empowerment measure in Central Sulawesi. The lo wer value subsequently marks an unreached goal in 2011-2016 Mid Term Development Plan of Central Sulawesi